2021
DOI: 10.1021/acs.energyfuels.1c03434
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Heavy Oil Using Oil-Dispersed Transition Metal Acetylacetonate Catalysts for Enhanced Oil Recovery

Abstract: In this work, several transition metal-based acetylacetonates (Ni, Cu, and Fe) were prepared as oil-dispersed catalysts for heavy oil oxidation. X-ray diffraction (XRD), scanning electron microscopy (SEM), and Mössbauer spectroscopy were used for the characterization of catalysts. The effectivity of catalysts in the oxidation of heavy oil was investigated by a thermogravimetry method coupled with infrared spectroscopy (TG-FTIR) at four different heating rates (4, 6, 8, and 10 °C/min) and self-designed porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The SARA analysis and viscosity of oil were conducted in accordance with ASTM D 4124 and ASTM D 445, respectively. 49 The initial and upgraded oils were evaluated for elemental composition (C, H, N, and S) using a PerkinElmer 2400 Series II analyzer according to ASTM (P/N 0240-1289). 9 2.2.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SARA analysis and viscosity of oil were conducted in accordance with ASTM D 4124 and ASTM D 445, respectively. 49 The initial and upgraded oils were evaluated for elemental composition (C, H, N, and S) using a PerkinElmer 2400 Series II analyzer according to ASTM (P/N 0240-1289). 9 2.2.…”
Section: Methodsmentioning
confidence: 99%
“…The used heavy crude oil was provided from the Tatarstan oil field (Russia), and its physical and chemical properties are listed in Table The silica gel particles (ACROS 24037) were purchased from TatchemProduct Co. (Russia). The SARA analysis and viscosity of oil were conducted in accordance with ASTM D 4124 and ASTM D 445, respectively . The initial and upgraded oils were evaluated for elemental composition (C, H, N, and S) using a PerkinElmer 2400 Series II analyzer according to ASTM (P/N 0240-1289) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Khelkhal et al also investigated the impact of bimetallic Mn@ Cu tallates, iron tallates, and copper tallates on crude oil combustion. Babapour Golafshani et al synthesized copper, nickel, and iron acetylacetonates and studied their catalytic effects as well as in situ transformation. The results indicated that acetylacetonate made an even dispersion of catalysts in an oil environment, and the catalysts reduced the reaction temperature of FD and HTO.…”
Section: Catalytic Oxidation Of Crude Oil Oxidationmentioning
confidence: 99%